2019
DOI: 10.1002/jsfa.9518
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of probiotic chocolate modulates intestinal physiological functions in constipated rats

Abstract: BACKGROUND This study investigated the in vivo prophylactic effect of probiotic chocolate on constipation. Rats were administered chocolate containing 2.5 × 1010 CFU g−1 of probiotics daily for 4 weeks and treated with loperamide (5 mg kg−1) daily at the fourth week of treatment. RESULTS Probiotic chocolate treatment significantly (P < 0.05) increased the intestinal motility, colon length, fecal moisture content and number of excreted fecal pellets in constipated rats. Moreover, quantitative real‐time polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…The mRNA expression levels of the targeted genes in tibia, ileum and colon tissues were determined as previously described (Lee et al . 2019). The genes and primer sequences used in the study are listed in Table (Ahmed and EL‐Maraghy 2013; Borges et al .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mRNA expression levels of the targeted genes in tibia, ileum and colon tissues were determined as previously described (Lee et al . 2019). The genes and primer sequences used in the study are listed in Table (Ahmed and EL‐Maraghy 2013; Borges et al .…”
Section: Methodsmentioning
confidence: 99%
“…2018; Lee et al . 2019). Relative mRNA expression levels of the targeted genes were calculated using Bid‐Rad CFX Manager software (Bio‐Rad, Hercules, CA); the mRNA levels of β‐actin gene (housekeeping gene) were used for normalization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in fecal pellet number, weight, and water content in rats with loperamide-induced constipation are important factors that need to be improved while aiming to relieve constipation. Previous studies have reported a marked reduction in the fecal pellet count, weight, and water content, in rats treated with loperamide [ 22 , 23 ], whereas prebiotic intake is known to improve the fecal parameters [ 24 , 25 ]. The MOS used in this study also improved the fecal pellet number and water content (Figures 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%